Electrophysiological monitoring in patients with tumors of the skull base treated by carbon-12 radiation therapy - Carozzo, Simone; Schardt, Dieter; Narici, Livio; Combs, Stephanie E.; Debus, Juergen; Sannita, Walter G. (International Journal of Radiation Oncology Biology Physics, 2013)
Purpose: To report the results of short-term electrophysiologic monitoring of patients undergoing 12C therapy for the treatment of skull chordomas and chondrosarcomas unsuitable for radical surgery. Methods and Materials: Conventional electroencephalogram (EEG) and retinal and cortical electrophysiologic responses to contrast stimuli were recorded from 30 patients undergoing carbon ion radiation therapy, within a few hours before the first treatment and after completion of therapy. Methodologies and procedures were compliant with the guidelines of the International Federation for Clinical Neurophysiology and International Society for Clinical Electrophysiology of Vision. Results: At baseline, clinical signs were reported in 56.6% of subjects. Electrophysiologic test results were abnormal in 76.7% (EEG), 78.6% (cortical evoked potentials), and 92.8% (electroretinogram) of cases, without correlation with neurologic signs, tumor location, or therapy plan. Results on EEG, but not electroretinograms and cortical responses, were more often abnormal in patients with reported clinical signs. Abnormal EEG results and retinal/cortical responses improved after therapy in 40% (EEG), 62.5% (cortical potentials), and 70% (electroretinogram) of cases. Results on EEG worsened after therapy in one-third of patients whose recordings were normal at baseline. Conclusions: The percentages of subjects whose EEG results improved or worsened after therapy and the improvement of retinal/cortical responses in the majority of patients are indicative of a limited or negligible (and possibly transient) acute central nervous system toxicity of carbon ion therapy, with a significant beneficial effect on the visual pathways. Research on large samples would validate electrophysiologic procedures as a possible independent test for central nervous system toxicity and allow investigation of the correlation with clinical signs; repeated testing over time after therapy would demonstrate, and may help predict, possible late toxicity. © 2013 Elsevier Inc. All rights reserved.
CRIS-Team Scopus Importer:2023-03-08